Adoption of cloud computing systems - Pedro Pinheiro; Aparicio, M.; Costa, C. (ISDOC '14 Proceedings of the International Conference on Information Systems and Design of Communication, 2014)
The purpose of this paper is to verify the factors that influence acceptance it in the context of cloud computing systems adoption. This study presents the theoretical factors, which influence the acceptance of new information systems. The first part contains a literature review on Cloud Computing. We describe the Technology Acceptance Model, applied with research hypothesis for an empirical study. The paper presents an empirical study conducted in a user dimension. Many users, professional and personal answered to a questionnaire from various fields. In this study, we concluded that perceived usefulness has a positive impact in the intention of using cloud computer systems, among other conclusions.